1994
DOI: 10.1177/109634809401700207
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Service Attribute Matrix To Measure Consumer Satisfaction

Abstract: Albrecht and Bradford's service attribute matrix was used to determine attributes leading to customer satisfaction and dissatisfaction in a college university foodservice. Customer satisfaction/dissatisfaction was measured from a self-administered questionnaire. Two hundred and twelve questionnaires were returned for a response rate of 66.7%. In general, the most important attributes to the customers in the university cafeteria were quality of food, convenient location, cleanliness, and reasonable price. Attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 4 publications
5
79
0
5
Order By: Relevance
“…Since the seminal work by Martilla and James (1977), the IPA framework has gained popularity among researchers in the hotel industry (Almanza, Jaffe, & Lin, 1994;Beldona & Cobanoglu, 2007;Chu & Choi, 2000;Hemmasi, Strong, & Taylor, 1994;Lewis, 1985;Martin, 1995), in tourism (Chon, Weaver, & Kim, 1991;Duke & Persia, 1996;Evans & Chon, 1989;Uysal et al, 1991;Wade & Eagles, 2003), the restaurant business (Hsu, Byun, & Yang, 1997;Keyt, Yavas, & Riecken, 1994), leisure and recreation (Fletcher, Kaiser, & Groger, 1992;Guadagnolo, 1985), education (Alberty & Mihalik, 1989;Kitcharoen, 2004;Ortinau, Bush, Bush, & Twible, 1989) and healthcare marketing (Dolinsky & Caputo, 1991;Hawes & Rao, 1985). Chu and Choi (2000) compared the importance and performance of 26 hotel attributes as perceived by business and leisure travellers in Hong Kong.…”
Section: Importance-performance Analysismentioning
confidence: 99%
“…Since the seminal work by Martilla and James (1977), the IPA framework has gained popularity among researchers in the hotel industry (Almanza, Jaffe, & Lin, 1994;Beldona & Cobanoglu, 2007;Chu & Choi, 2000;Hemmasi, Strong, & Taylor, 1994;Lewis, 1985;Martin, 1995), in tourism (Chon, Weaver, & Kim, 1991;Duke & Persia, 1996;Evans & Chon, 1989;Uysal et al, 1991;Wade & Eagles, 2003), the restaurant business (Hsu, Byun, & Yang, 1997;Keyt, Yavas, & Riecken, 1994), leisure and recreation (Fletcher, Kaiser, & Groger, 1992;Guadagnolo, 1985), education (Alberty & Mihalik, 1989;Kitcharoen, 2004;Ortinau, Bush, Bush, & Twible, 1989) and healthcare marketing (Dolinsky & Caputo, 1991;Hawes & Rao, 1985). Chu and Choi (2000) compared the importance and performance of 26 hotel attributes as perceived by business and leisure travellers in Hong Kong.…”
Section: Importance-performance Analysismentioning
confidence: 99%
“…A positive disconfirmation occurs if the product or service is better than expected, whereas a performance worse than expected results in a negative disconfirmation. A review of recent hospitality literature, notably by Barsky (1992Barsky ( , 1995, Almanza et al (1994), Bojanic and Rosen (1994), Dube et al (1994), Lee and Hing (1995), Stevens et al (1995), Johns (1996), Johns and Tyas (1996), Oh and Jeong (1996), Pettijohn et al (1997), andQu (1997), suggests that customer satisfaction research is important because it is directly linked to return behavior.…”
Section: Sharma and Stafford (2000)mentioning
confidence: 99%
“…Author/effect Theory/referenced literature Relevance Findings Kivela, Inbakaran and Reece (1999) However, the literature also reveals that there is little theoretical understanding about the disconfirmatory effects on the formation of dining satisfaction, and how satisfaction affects post-dining Similarly, Almanza et al (1994), Dube et al (1994), Lowenstein (1995), Lee and Hing (1995), Oh and Jeong (1996), Yau and Lee (1996), Pettijohn et al (1997) and Qu (1997), have identified customer satisfaction to be behavioral intentions, prompting Oh and Jeong (1996) to lament at the paucity of studies specifically concerned with dining satisfaction and return patronage" (p. 206).…”
Section: (Table Continues) (Continued)mentioning
confidence: 99%
“…Lewis and Chambers (1989) reported the effective use of IPA by the Sheraton Hotel in monitoring customer satisfaction. Almanza, Jaffe and Lin (1994) used the IPA matrix to determine means for improving customer satisfaction. Martin (1995) examined service providers' perceptions of customers' expectations of quality service in the hotel industry using the IPA technique.…”
Section: Importance-performance Analysis (Ipa)mentioning
confidence: 99%